Justification by Faith - How early? An exegetical and chronological Contribution to the Reformation Anniversary - Riesner, Rainer (Vox Scripturae - Revista Teológica Internacional, 2018)
The Letter to the Galatians was written about 48 AD, before the Apostolic Council and soon after the Antiochian incident. This is one reason why the report of Paul of this incident should be regarded as reliable. As in other cases of fundamental conflict, the Apostle argued not only with his own theological reflection, but also appealed to a common foundation, referring to a basic conviction in Galatians 2.16a: „We know that a man is not justified by observing the law, but by faith in Jesus Christ.“ The phrasing of this shared conviction may possibly go back to the early Jerusalem church, where from the beginning a dissociation from the Essenic understanding of justification was required. For the essential elements of this basic conviction one could rely on the Jesus tradition. Jesus had understood himself as the messianic Servant who, according to Isaiah 53.11, „justifies the many.“ Even before Easter, the belief that God had empowered Jesus in a unique way meant access to healing and salvation. The formation of a reflected doctrine of justification in the Galatian crisis was the great theological achievement of Paul, but he was able to draw upon traditions of the early Jerusalem church and the Jesus tradition.
Keywords: Justification; Galatians; Paul; Peter; James; Apostolic Council